1984
DOI: 10.1590/s0074-02761984000400011
|View full text |Cite
|
Sign up to set email alerts
|

The vertical dispersión of Anopheles (Kerteszia) cruzi in a forest in southern Brazil suggests that human cases of malaria of simian origin might be expected

Abstract: By staining females of Anopheles cruzi with fluorescent coloured powders in a forest in the State of Santa Catarina, we showed that they move from canopy to ground and vice-versa to feed. This suggests that in areas where this mosquito is a vector of human and simian malarias sporadic infections of man with monkey plasmodia might be expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1
10

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 1 publication
0
29
1
10
Order By: Relevance
“…Unlike the fi ndings of previous studies in Southeastern Brazil (Deane et al 1984, Deane 1992, Tubaki et al 1993, our results showed a decrease in frequency of A. cruzii / A. homunculus as the distance from the forest and canopy increased, refl ecting their limited domiciliary habits and vertical dispersal. However, other species, such as A. strodei, were found to display different behavior, with their frequency increasing near houses and decreasing inside the forest, indicating possible replacement of A. cruzii by other species.…”
Section: A Cruzii/a Homunculuscontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike the fi ndings of previous studies in Southeastern Brazil (Deane et al 1984, Deane 1992, Tubaki et al 1993, our results showed a decrease in frequency of A. cruzii / A. homunculus as the distance from the forest and canopy increased, refl ecting their limited domiciliary habits and vertical dispersal. However, other species, such as A. strodei, were found to display different behavior, with their frequency increasing near houses and decreasing inside the forest, indicating possible replacement of A. cruzii by other species.…”
Section: A Cruzii/a Homunculuscontrasting
confidence: 99%
“…It appears that the other species, unlike A. cruzii / A. homunculus, can adapt more easily and live in areas modifi ed and inhabited by human beings (Deane et al 1984, Guimarães et al 2000, Forattini 2002. Based on this assumption, our fi ndings may demonstrate the replacement of A.…”
Section: A Cruzii/a Homunculusmentioning
confidence: 99%
“…cruzii, espécie vetora natural de malária simiana na região Neotropical, o ecletismo e a mobilidade vertical entre solo e copa das árvores tornam possível a ocorrência de infecção humana por plasmódios de macacos em áreas com ocorrência de malária simiana. 5 De acordo com a Superintendência …”
Section: Abstract: Anopheles Insect Vectors Ecology Vertical Distrunclassified
“…Studies on seasonal and vertical distribution of An. cruzii demonstrated high vertical mobility from ground level to tree tops and this behavior could be responsible for human infection by simian Plasmodium species (Deane et al, 1984;Marrelli et al, 2007;Ueno et al, 2007).…”
Section: Introductionmentioning
confidence: 99%